2018
DOI: 10.1530/ey.15.13.20
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide trends in body-mass index, underweight, overweight, and obesity from 1975 to 2016: a pooled analysis of 2416 population-based measurement studies in 128.9 million children, adolescents and adults

Abstract: Background Underweight, overweight, and obesity in childhood and adolescence are associated with adverse health consequences throughout the life-course. Our aim was to estimate worldwide trends in mean body-mass index (BMI) and a comprehensive set of BMI categories that cover underweight to obesity in children and adolescents, and to compare trends with those of adults. Methods We pooled 2416 population-based studies with measurements of height and weight on 128•9 million participants aged 5 years and older, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 35 publications
0
41
0
7
Order By: Relevance
“…It is well known that obesity is a major risk factor for NAFLD [31]. BMI is useful indicator for evaluating obesity and nutritional status [32], and there is a strong relationship between BMI and prospectively recorded diagnoses of NAFLD [33]. We found that there was a close relationship between ALT and BMI.…”
Section: Discussionmentioning
confidence: 52%
“…It is well known that obesity is a major risk factor for NAFLD [31]. BMI is useful indicator for evaluating obesity and nutritional status [32], and there is a strong relationship between BMI and prospectively recorded diagnoses of NAFLD [33]. We found that there was a close relationship between ALT and BMI.…”
Section: Discussionmentioning
confidence: 52%
“…Between 1975 and 2016, a global increase in the number of children and adolescents (5–19 years) was estimated in approximately 113 million cases. 1 , 2 Brazilian population-based surveys indicate prevalence of overweight ranging from 15.3 and 20.5% in this age group. 1 Caloric intake from foods of low nutritional quality and physical inactivity contribute significantly to these rates.…”
Section: Introductionmentioning
confidence: 91%
“…1 Caloric intake from foods of low nutritional quality and physical inactivity contribute significantly to these rates. [1][2][3] Ultra-processed foods (UPF) are among these foods, and, according to the NOVA classification, they are industrial formulations rich in sugars, fats and sodium and low in micronutrients, bioactive compounds and fibers. In addition, they have attractive characteristics such as high palatability, sophisticated packaging, good marketing and ease of access, which encourage excessive consumption and substitution of traditional food kinds.…”
Section: Introductionmentioning
confidence: 99%
“…Being underweight among children and adolescents is associated with an increased susceptibility to fat accumulation, lower fat oxidation, lower energy expenditure, a higher risk of insulin resistance in adulthood, dyslipidemia, and hypertension [18]. Globally, in 2016, the prevalence of moderate and severe underweight was 8.4% in girls and 12.4% in boys [19]. According to Rokholm et al, the rise in excess body weight in children and adolescents has plateaued in high-income countries but continues in low-income and middle-income countries, and the relatively rapid transition from underweight to excessive body weight in low-income and middle-income countries has been noted [20].…”
Section: Discussionmentioning
confidence: 99%